RELATIONSHIP BETWEEN HUSBAND AND HEALTH WORKERS' SUPPORT WITH MOTHER'S INTEREST IN USING IUD CONTRACEPTION - ruri maiseptya sari (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Intrauterine Contraception Device (IUD) is a method of contraception that is quite safe and is the most recommended in the national family planning program in Indonesia. This study aims to study the significant relationship between the support of husbands and health workers with mothers' interest in using IUD contraception in the working area of the Taba Lagan Health Center, Central Bengkulu Regency. The approach of this study used a descriptive correlation with a cross sectional approach. The population in this study were all couples of childbearing age who came to visit the Taba Lagan Health Center in February 2022, as many as 91 people were taken using accidental sampling. Data collection in this study uses primary data by distributing questionnaires. Data analysis was carried out by the Chi Square test (x) with the Contingency Coefficient test (c). The results of the study from 91 samples there were 53 people with low interest, 52 husbands did not support and 72 people got good information from health workers. The results of the Bivariate analysis show that there is husband support in the very weak category, and information on health workers in the weak category in the working area of the Taba Lagan Health Center, Central Bengkulu Regency. It is hoped that they can use appropriate contraception according to the age and parity of the mother to manage pregnancy spacing and reduce the impact of contraceptive use on mother's health